Profile of Students’ Science Process Skills on Conventional Biotechnology Material - E. Astika; H. K. Surtikanti; K. Kusnadi; N. S. Putra (Universitas Negeri Yogyakarta, 2022)
The study aimed to find out students’ science process skill profile in grade XII. The research was conducted at SMAN 1 Tanah Putih Tanjung Melawan, Riau. The study was conducted by providing tests to students consisting of 10 questions on the scope of conventional biotechnology materials. This test used to measure students' science process skills, namely the ability to observe, communicate, interpret, propose hypotheses, apply concepts, ask questions, predict, use tools/materials, plan experiments, and classify. The research sample consisted of 70 students. The reliability value of the instrument was 0.948 of high category. It was obtained that the science process skill of students was categorized as medium with a percentage of 39.3%. The percentage of observing, communicating, interpreting, formulating hypotheses, applying concepts, asking questions, predicting, using tools/materials, planning experiments, and classifying abilities were 43.2%, 35.4%, 39.3%, 28.2%, 26.8%, 36.8%, 46.4%, 49.6%, 37.1%, and 50%, respectively. Some of the science process skill aspects showed a low category, namely in the aspects of formulating hypotheses and applying concepts. Other aspects showed medium category and almost all aspects were below 50%. The teacher’s role was very decisive as the main actor in improving students’ science process skills.